Comparative Study of Immune-Diagnostic Tools with Polymerase Chain Reaction in Sub-Clinical Leishmaniasis Isolates - Abdalla, Nazar M (Journal of Medicine, 2011)
Objective: This study aimed to identify cases of leishmaniasis in the Nuba Mountain area, which is situated in a unique geographical site located in the centre of Sudanese leishmania belt. Wide range of investigations are available for detection of leishmania cases, but still the most reliable and easy test used as screening and epidemiological tool in field studies needs to be evaluated. The most commonly used conventional diagnostic methods direct microscopy and culture have some drawbacks in diagnosing subclinical cases of leishmaniasis. Materials and methods: In this study, comparative properties of various immune-diagnostic tools with Polymerase Chain Reaction used in sub-clinical leishmaniasis isolates were explored. The immune-diagnostic tools involved in this study include- Leishmanin Skin Test (LST), Enzyme Linked Immunosorbent Assay (ELISA) and Direct Agglutination Test (DAT). The study was conducted in the Green Valley village (Rashad Province, South Kordofan State) with a population of 332. Most of the villagers presented with sub-clinical form of leishmaniasis with minor symptoms and signs without the features found in clinical form of visceral leishmaniasis such as fever, diarrhoea, epistaxis, enlarged lymph nodes, spleen and liver. In this study we collected demographic, clinical and epidemiological data using special questionnaire. Leishmanin skin test (LST), ELISA, DAT and PCR for parasite DNA detection were used. Result: The final positive cases detected by PCR were 32 out of 332 belong to L. donovani species. The final positive cases detected by LST were 51.2% of the total population under study, while 11 out of the 37 tested samples were positive by ELISA. All of the 332 villagers showed negative readings by DAT with exception of three individuals who were positive with very high titers. Conclusion: DNA etxtraction and amplification with primers can be a good screening tool in subclinical leishmaniasis isolates. Keyword: Sub-clinical; Leishmaniasis; Leishmanin Skin Test; ELISA; DAT; PCR. DOI: 10.3329/jom.v12i1.5422 J Medicine 2011; 12 : 34-39